Development of a nanobiosensor for detection of banana bunchy top virus - Vinusri S (Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, 2016)
The investigations on ‘Development of a nanobiosensor for detection of Banana bunchy top virus’ were conducted at the Centre for Plant Biotechnology and Molecular Biology (CPBMB), College of Horticulture, Kerala Agricultural University, Thrissur and Centre for Materials for Electronics Technology(C-MET), Thrissur during August, 2014 to June, 2016. The objective of the study was to develop a nanobiosensor for easy and quick detection of Banana bunchy top virus (BBTV). Biosensors based on Localised Surface Plasmon Resonance (LSPR) have gained much attention now-a-days. Gold nanoparticles are ideal for optical sensing due to their better light absorption and scattering properties, chemical stability, high surface to volume ratio and high surface energy to provide stable immobilization of large amount of biomolecules. In the present study, a solution phase LSPR biosensor using gold nanorods (GNRs) was developed for detection of BBTV. Gold nanorods were synthesized using seed mediated growth method. The concentration of silver nitrate and volume of seed solution required to synthesize stable GNRs were optimized in the present study. The characterization of GNRs was done using UV-Vis spectrophotometry and Transmission Electron Microscopy. Two absorption bands were observed in the absorption spectrum of GNRs. The longitudinal plasmon band was observed at 679 nm and the transverse plasmon band was observed at 515 nm. The mean length, width and aspect ratio of the synthesized GNRs recorded using transmission electron microscopy were 35.84 nm, 13.57 nm and 2.64 respectively. Surface modification of CTAB capped GNRs was done by ligand exchange method. Functionalization of GNRs with BBTV specific antibody was undertaken by conjugating the antibody with GNRs to make a GNR probe. Dilution of antibody required for conjugation with GNRs was standardised as 1:100. Development of LSPR based biosensor using GNRs was attempted as chip based and solution phase based. As immobilization of GNRs on glass surface was not successful, studies on chip based biosensor could not be continued and further focus was made on solution phase LSPR biosensor. The BBTV antigen was isolated from the BBTV infected samples of banana collected from Banana Research Station of Kerala Agricultural University. The isolated antigen was allowed to interact with GNR probe and it was found that LPB was more sensitive to the interaction. Different concentrations of antigen were allowed to interact with GNR probe solution to identify the minimum detection limit. The efficacy of solution phase LSPR biosensor in detecting the antigen was further checked with BBTV infected leaf samples of six different banana cultivars viz. Yangambi Km5, Chenkadali, Nendran, Palayamkodan, Grand Naine and Kunnan. The kinetics of interaction of GNR probe with antigen from different banana cultivars and characterization of the interaction with UV-Vis spectrophotometry revealed that the developed biosensor was able to detect very low concentration of antigen (0.02 mg/ml) within a period of five to ten minutes. Colour change was also noticed due to interaction of GNR probe with antigen. In the infected samples, colour change from pinkish red to pale grey was evident while no such colour change was noticed in healthy samples. Due to the colour change, the developed solution phase sensor as such can be used for field level applications. The efficacy of developed solution phase LSPR based GNR biosensor was compared with Enzyme Linked Immuno Sorbent Assay (ELISA) for detecting BBTV antigen. The detection limit of antigen in ELISA was 0.08 mg/ml (80 ppm) while in the developed biosensor the detection limit was 0.02 mg/ml (20 ppm). The solution phase LSPR based GNR biosensor developed in the present study is thus effective for easy and quick detection of BBTV. Conversion of solution phase based GNR biosensor to chip based sensor will open up more applications and will help for easy commercial fabrication. Multiplexing is also possible in chip based sensor by controlling the aspect ratios of GNRs and functionalising with different antibodies specific to different pathogens so that the sensor can detect multiple pathogens using a single chip. The technology generated from the present investigations for the development of LSPR based GNR biosensor could be applied in other crops/ other pathogens with modifications